Maternal Perception of Medicinal Foods in Child Feeding Practices: A Study in Marsabit County, Kenya - Chepkorir, Rose; Onyango, Agatha Christine; Masinde, David; Musita, Caroline Patricia (European Scientific Journal, ESJ, 2025)
Medicinal foods are important for enhancing children’s health and preventing common illnesses. However, there is a lack of comprehensive understanding regarding how mothers perceive these foods and their effectiveness in child nutrition. Therefore, this study aimed to determine maternal perception of medicinal foods used in child feeding. This study adopted a cross-sectional study design. A three-stage sampling technique was used to randomly select 278 eligible households with children aged 6–24 months to assess their perception of child feeds with medicinal value. A questionnaire was used to gather quantitative data. Focus Group Discussion and Key Informant Interview guides were used to collect qualitative data. Univariate analysis was used to obtain the frequency distribution of maternal perception of medicinal foods. The results indicated that the common childhood illnesses in the community are diarrhea 63.9%, Pneumonia 55.2%, malnutrition 35.1%, malaria 35.7%, anemia 35.7%, and common cold 24.2%. Findings show that 56% of the respondents offered foods for medicinal purposes to their children during sickness and in good health. Most (75.5%) respondents indicated plants, fruits, and foods were used for medicinal purposes. The study concludes that maternal perceptions of medicinal foods significantly influence child-feeding practices in Marsabit County, Kenya. Based on the findings, the study recommends that the Marsabit County government conduct scientific research and clinical trials to assess the efficacy and safety of local plants, fruits, and foods used by mothers to treat childhood illnesses and integrate evidence-based findings into community health education. This study had potential limitations. It relied on maternal responses, which could have been affected by recall or social desirability bias; however, engaging communities in discussions on child nutrition can help bridge gaps between perception and scientific evidence, leading to informed decision-making. This initiative should involve collaboration between the local health authorities, research institutions, and traditional knowledge holders.